Analisis Perbandingan Optimalisasi Port Knocking Dan Honeypot dengan Iptables Pada Server Untuk Keamanan Jaringan - Anjun Dermawan; Y Yuhandri; S Sumijan (LPPM STIKOM Tunas Bangsa, 2024)
Computer network systems are designed to share resources together, so that the security of resources on the server must be maintained and the resources used must be optimized. The aim of this research is to analyze the comparative level of optimization of Port knocking and Honeypot using the IPTables method for network security on servers with different CPU and memory resources. The security methods used in this research are Port knocking, Honeypot and IPTables. The data used includes ports that were successfully attacked as well as resource usage before and after IPTables implementation on a server with 2 CPU resources and 1507284KiB memory obtained from previous research. The results of this research show that 80% of ports cannot be attacked while 20% of ports, namely port 22, are designed to be attacked. The server CPU and Memory resource usage graph shows a decrease after implementing IPTables from Denial of Service (DoS) and Brute force testing. On a server with 1 CPU and 1015852KiB of memory resources, CPU usage decreased by 36%, and memory usage decreased by 41%. Meanwhile, on a server with 4 CPU resources and 6036624 KiB of memory, CPU usage decreased by 41%, and memory usage decreased by 46%. This shows increased effectiveness compared to using just the Port knocking and Honeypot methods. It is hoped that this research can be a guide in measuring server optimization in overcoming Denial of Service (DoS) and Brute force attacks